2016
DOI: 10.1080/10245332.2016.1142710
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene polymorphisms and the risk of vasculopathy in sickle cell disease

Abstract: eNOS intron 4 and eNOS T>C gene polymorphisms may be used as a genetic marker of prognostic value in SCD, as they are associated with unfavorable clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
11
1
2
Order By: Relevance
“…Published reports from our group and others, have shown that there is a significant interethnic diversity in the distribution of eNOS variants 16 , 17 , 18 , 19 and this could be potential contributor to differing sickle cell pathophysiology. 19 Despite the reports from other populations, 4 , 5 , 8 , 9 , 10 , 11 we showed previously that there is no difference in the genotypic or allelic frequencies of eNOS and endothelin-1 variants or significance of both polymorphisms among sickle cell disease patients from Africa. 20 If this is the case, do endothelial nitric oxide synthase and endothelin-1 gene polymorphism contribute to clinical pathophysiology among phenotypically-related African Americans with sickle cell disease?…”
Section: Introductioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Published reports from our group and others, have shown that there is a significant interethnic diversity in the distribution of eNOS variants 16 , 17 , 18 , 19 and this could be potential contributor to differing sickle cell pathophysiology. 19 Despite the reports from other populations, 4 , 5 , 8 , 9 , 10 , 11 we showed previously that there is no difference in the genotypic or allelic frequencies of eNOS and endothelin-1 variants or significance of both polymorphisms among sickle cell disease patients from Africa. 20 If this is the case, do endothelial nitric oxide synthase and endothelin-1 gene polymorphism contribute to clinical pathophysiology among phenotypically-related African Americans with sickle cell disease?…”
Section: Introductioncontrasting
confidence: 62%
“… 10 In fact, a study from India found an association between eNOS gene polymorphisms and sickle cell disease severity, 4 concluding that eNOS gene is a genetic modifier of phenotypic variation among patients, or a marker of prognostic value, based on association with SCD clinical outcome. 11 Endothelin-1 (rs5370) gene is another whose polymorphism has been implicated in disease pathophysiology, including progression of chronic glomerulosclerosis, 12 pulmonary hypertension 13 , 14 and vaso-occlusive episodes correlated with pain history. 15 Its G5665T and T8002C variants have been associated with abnormal vascular reactivity, while the C8002 allele appears to increase the risk of acute chest syndrome in sickle cell disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these include 786T>C (rs2070744) in promoter region, 894G>T in exon 7 (Glu-298Asp, rs1799983), and 4a/b, a 27-bp variable number of tandem repeats in intron 4 (chromosome 7q35–q36). 35 Nishank et al 36 found that there was a higher frequency of these particular polymorphisms in patients with severe SCD who had significantly lower levels of plasma nitrite compared to those in the mild SCD group. The homozygous 786T>C polymorphism decreases eNOS activity, leading to lower NO levels.…”
Section: No Inducersmentioning
confidence: 99%
“…Ме-та-анализ, посвященный выявлению участия по-лиморфизма 4а/b в развитии рака простаты, пока-зал наличие высокой положительной связи меж-ду данным заболеванием и вариантом 4а4а+4а4b (ОШ=1,47, 95% ДИ=1,00-2,14, р=0,05), также установлено, что носители аллеля «а» имеют повышенный риск прогрессирования рака [27]. Повышенная предрасположенность к развитию рака предстательной железы и полиморфизма 4а/b (4а4b в сравнении с 4b4b, ОШ=1,338; 95% ДИ=1.013-1.768; 4а4а + 4а4b в сравнении с 4b4b: ОШ=1,474, 95% ДИ=1.002-2,170) показана в ра-боте [28].…”
Section: характеристика полиморфного локуса т786с гена эндотелиальнойunclassified
“…В исследовании S. M. Yousry et al [28] вы-явлено, что генотип 4a4а оказывает защитный эффект у пациентов с серповидно-клеточной анемией при сосудисто-окклюзионном кризисе и легочной гипертензии, при этом мутантный гомозиготный гаплотип С-4a (аллель C поли-морфизма Т786С и аллель-4a полиморфизма 4а/b) в значительной степени ассоциирован с риском развития острого грудного синдрома, сосудисто-окклюзионного кризиса и легочной гипертензии. Носители минорного аллеля «а» полиморфизма 4а/b имеют значительно более низкие значения индекса активности ревматоид-ного артрита (DAS28) [38].…”
Section: характеристика полиморфного локуса т786с гена эндотелиальнойunclassified